Measure Post-Bloodmeal Dispersal of Mosquitoes and Duration of Radioactivity by Using the Isotope 32P. Issue 1 (25th November 2014) - Zhang, Chongxing; Cheng, Peng; Liu, Bo; Shi, Guihong; Wang, Huaiwei; Liu, Lijuan; Guo, Xiuxia; Ren, Huiqing; Gong, Maoqing
Abstract : The radioactive isotope 32 P-labeled disodium phosphate (Na2 H 32 PO4 ) was injected via the jugular vein into a cow kept in a shed in Maozhuang Village, Cao Township of Shanxian County, China. Over the following 5 d, mosquitoes feeding on the cow were captured at distances up to 400 m to determine dispersal distance. The duration of radioactivity in the cow and marked mosquitoes was 10 d. The results showed that after blood feeding, Anopheles sinensis and Culex tritaeniorhynchus temporarily rested in the cattle shed and then flew outdoors. In contrast, Culex pipiens pallens remained in the cattle shed after feeding. These findings confirmed that local An. sinensis and Cx. tritaeniorhynchus were partially endophilic and tended to rest out of doors, whereas Cx. pipiens pallens was endophilic. For marked An. sinensis and Cx. tritaeniorhynchus, there was a significant tendency for dispersal to be in a northeast and east direction, probably because of the presence of heavy shading by an agricultural field, a small river for mosquito oviposition sites, and locations downwind from the blood source. The furthest flight distances for An. sinensis and Cx. tritaeniorhynchus were 210 and 240 m; therefore, control of these mosquitoes should include resting places indoors and outdoors within a radius of 250 m from confirmed cases.